Quality of systematic review and meta-analysis abstracts in oncology journals. (2016) - Koller, Chelsea; Khan, Sarah; Holmes, Jonathan; Herrmann, David; Vassar, Matt
Abstract: Purpose: The purpose of this study was to evaluate the quality of reporting in the abstracts of oncology systematic reviews using PRISMA guidelines for abstract writing. Methods: Oncology systematic reviews and meta-analyses from four journals - The Lancet Oncology, Clinical Cancer Research, Cancer Research, and the Journal of Clinical Oncology - were selected using a PubMed search. The resulting 337 abstracts were sorted for eligibility and 182 were coded based on a standardized abstraction manual constructed from the PRISMA criteria. Eligible systematic reviews were coded independently and later verified by a second coder, with disagreements handled by consensus. One hundred eighty-two abstracts comprised the final sample. Results: The number of included studies, information regarding main outcomes, and general interpretation of results were described in the majority of abstracts. In contrast, risk of bias or methodological quality appraisals, the strengths and limitations of evidence, funding sources, and registration information were rarely reported. By journal, the most notable difference was a higher percentage of funding sources reported in Lancet Oncology . No detectable upward trend was observed on mean abstract scores after publication of the PRISMA extension for abstracts. Conclusion: Overall, the reporting of essential information in oncology systematic review and meta-analysis abstracts is suboptimal and could be greatly improved.